Frequencies of Human Leukocyte Antigen Alleles in Turkish Children with Kawasaki Disease - Teke, Türkan Aydın; Tan, Çağman; Aydın, Zeynep Gökçe Gayretli; Kaman, Ayşe; Özbek, Begüm; Öz, Fatma Nur; Çağdaş, Deniz; Tanır, Gönül; Tezcan, İlhan (Journal of Pediatric Infectious Diseases, 2024)
Objective Kawasaki disease (KD) is an acute systemic vasculitis that is one of the major causes of acquired heart disease especially in young children. The pathogenesis of KD is still unclear. The increased incidence of the disease among Japanese children and siblings of affected patients suggests a genetic component to KD susceptibility. Several reports have studied human leukocyte antigen (HLA) polymorphisms in different populations with KD and found various results. In the present study, we aimed to evaluate the association of HLA-A, -B, -C, -DRB1, and -DQB1 allele frequencies in Turkish children with KD.Methods The study was conducted between January 2016 and February 2018. HLA Class I (A, B, and C) and Class II (DRB1 and DQB1) alleles of patients and healthy controls were studied using the low-resolution DNA-based sequence-specific oligonucleotide method.Results Fifty children with KD and 500 healthy controls were included in this study. In the analysis of HLA-A, HLA-B, HLA-C, and HLA-DRB1 alleles, no statistical difference was found in the frequency of alleles between the patients with KD and the control group. However, a significantly lower frequency of the HLA-DQB1*03 allele was observed in the KD group than in the control group (p < 0.001, odds ratio [OR]: 0.29, 95% confidence interval [CI]: 0.15–0.55). When the patients with KD were divided into two subgroups with or without coronary artery lesions (CALs), the frequency of the HLA-DQB1*03 allele was also found lower in the KD group with CALs than the KD group without CALs (p = 0.008, OR: 0.19, 95% CI: 0.05–0.68).Conclusion The study may guide future studies on HLA-DQB1*03 whether it is a protective allele for KD and CALs in Turkish children.
Keywords: Kawasaki disease; coronary artery lesion; HLA allele; Turkish children